Antigua and Barbuda : 2010 Article IV Consultation and Request for Stand-By Arrangement; Staff Report; Supplements; Public Information Notice; Press Release; and ED's Statement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The global slowdown has severely affected Antigua and Barbuda's economy through its impact on tourist arrivals, FDI inflows and remittances, and fiscal revenue. The recession and associated fiscal crisis coincides with already weak public finances and mounting problems in the financial sector. The authorities have taken decisive action to address the fiscal crisis and set the stage for a sustained recovery. The scope for restructuring public debt with domestic banks is limited, and financial sector reform is paramount.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet